DESIGN AND ANALYSIS OF CHASSIS FRAME FOR CHOPPER-STYLE MOTORCYCLE - Rahmadi, Apri; Mursalin, Mursalin (Universitas Muhammadiyah Surakarta, 2024)
Other than being a means of transportation, motorcycles represent a lifestyle for automotive enthusiasts. One way these enthusiasts express their passion is by customizing motorcycles. One common modification involves altering the motorcycle's original form, known as a custom-built motorcycle. There are several types of custom-built motorcycles, including cafe racers, street trackers, scramblers, bobbers, and choppers. Of these types, chopper-style motorcycles typically use a frame chassis which is built from scratch. This research aims to design and analyze the frame of a custom chopper-style motorcycle. The process involves creating a 3D model and analyze the strength of chassis frame using the Finite Element Method (FEM) by using Autodesk Inventor Professional 2022 software. The engine mass supported by the frame is assumed to be 30 kg. The frame is assumed to be ridden solo and with a passenger, resulting in total rider weights of 70 kg, 90 kg, 140 kg, and 180 kg. The result of this research is a chopper motorcycle frame design made of steel, weighing 11.74 kg, capable of supporting a rider's load of up to 140 kg, with a safety factor value of 3.20.